Estimating the exchange rate pass-through into inflation in Vietnam - Tran, Mai Anh (ĐHQG, 2016)
This paper analyzes the degree and timing of the responses of import prices and consumer prices to changes in the exchange rate in Vietnam. The vector auto regression (VAR) technique is applied to examining the exchange rate pass- through. The research results that the average exchange rate pass-through to import prices and consumer prices are 0.13 and 0.065 respectively in the first 6 months, staying at the fairly low level as compared with other economies. The largest impacts to domestic prices are on 8th month in term of import prices and 9th month in the case of consumer prices after the exchange rate shock. Moreover, exchange rate shock affects to inflation almost through the indirect channel of the high dollarization in the whole economy. Therefore, controlling inflation and stabilizing prices may reduce the impact of the exchange rate shock to domestic prices. In addition, this paper recommends that the SBV should adopt an exchange rate policy with a larger band.